Polypyrrole Functionalized Graphene Oxide Accelerated Zinc Phosphate Coating under Low-Temperature - Zhu, Qingsong; Liu, Jingguang; Wang, Xin; Huang, Yuxiang; Ren, Ying; Song, Weiqiang; Mu, Chenzhong; Liu, Xianhu; Wei, Fengchun; Liu, Chuntai (ES Materials & Manufacturing, 2020)
Zinc phosphate coating, as an effective and fast anticorrosion technique for the metals, have been developed rapidly in recent years. However, it is still a challenge to synthesize a low energy, environmentally friendly and efficient accelerator through a facile method. Herein, as a new accelerator, polypyrrole (PPy) functionalized graphene oxide (GO-PPy) nanocomposites were prepared by in-situ process to grow PPy film on GO surface, Incorporation of GO-PPy into phosphate baths accelerated the phosphating process of phosphate coating and promoted the nucleation and growth of phosphate crystals, achieving stronger corrosion resistance, which were confirmed by electrochemical measures and morphologies characteristic of the phosphate coating. Additionally, when the concentration of GO-PPy in the phosphate baths reached up 1.2 g/L, the phosphate coating possessed the most compact and uniform phosphate crystals and the best corrosion protection performance. Finally, the special mechanism of the phosphate process was discussed. This work introduces a new, low-energy, facile, environmentally friendly and alternative accelerator for the preparation of phosphate coatings.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Accelerate; Corrosion protection; Phosphate coating; Phosphate crystals